Dispersion liquid, method for producing same, and cured product thereof
By using a dispersion made of surface-treated titanium oxide particles, silane coupling agents and polymerizable monomers in electronic device sealing materials, the problem of difficulty in balancing high refractive index and transparency in the existing technology is solved, and low viscosity and A dispersion of low volatility solvents suitable for sealing optical components.
Patent Information
- Application Number
- CN202380046683.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-15
- Filing Date
- 2023-06-14
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to reduce the viscosity of titanium oxide particles in the dispersion and the content of volatile solvents, especially when manufacturing sealing materials for electronic devices while maintaining high refractive index and transparency.
By using the surface -treated titanium oxide particles, a silane coupling agents, and a decentralized liquid made of a monomer with aggregate functional groups, the dispersed solution is burned at high temperature to reduce the viscosity, and it is replaced by the replacement of organic solvents to reduce the volatile component. Essence
Differentians with high refractive index, excellent transparency, low viscosity, and low volatile solvent content are suitable for sealing materials for electronic devices, especially in sealing applications of optical components.
Smart Images

Figure BDA0005184545530000231 
Figure BDA0005184545530000241 
Figure BDA0005184545530000251
Abstract
Description
Technical Field
[0001] The present invention relates to a dispersion containing titanium oxide particles and a method for producing the same, and also to a curable sealing material composed of the dispersion and further to a cured product obtained by curing the dispersion. Background Art
[0002] Many electronic devices are susceptible to degradation due to oxygen or moisture, and therefore are widely protected by sealing materials made of curable resins. Various sealing materials are known for this purpose, depending on the application.
[0003] For example, in the case of an optical element, since the luminescent material is easily degraded by moisture and oxygen, it is necessary to seal the optical element. In the case of sealing an optical element, from the perspective of brightness or clarity, it is important to effectively take out the light emitted from the element to the outside. Therefore, the sealing material is required to have transparency and a high refractive index. By having a high refractive index, the refractive index difference between the high refractive index component constituting the optical element and the sealing material can be reduced to reduce the light loss caused by reflection or refraction.
[0004] Therefore, as a sealing material for optical elements, various sealing materials with excellent transparency while having a high refractive index have been proposed so far. For example, a resin composition is described in patent document 1, which includes: a compound containing multiple sulfur atoms and aromatic rings and having a reactive functional group, a compound having a polymerizable double bond and an aromatic ring, and a photocationic polymerization initiator, and a high-refractive-index cured product is obtained by curing it, which can be used as a sealing material for an organic EL element. In addition, an epoxy polymerizable composition is described in patent document 2, which includes: a S-containing epoxy compound, a thiol compound having multiple thiol groups in one molecule, and a curing accelerator, and the refractive index of the cured product is high, which can be used as a sealing material for an organic EL element. Patent document 2 also describes: by further mixing a silane coupling agent in the composition, the adhesion with a substrate, etc. can be improved. However, in order to manufacture these compositions, it is necessary to use special compounds.
[0005] In addition, in Patent Document 3, as a sealing material for an organic EL element, a curable composition is described, which comprises: a compound having a polymerizable double bond bonded to a naphthalene ring and a polymerization initiator, the curable composition is solvent-free and low-viscosity, and the resulting cured film is a high refractive index. It is also described that by further admixing the composition described in Patent Document 3 with metal oxide particles having a primary particle size of less than 100 nm and a refractive index of more than 1.6, such as titanium oxide particles, the refractive index of the resulting cured product can be further increased. However, it is difficult to disperse titanium oxide particles to the order of tens of nm, and it is not easy to obtain a cured product admixed with titanium oxide particles and having excellent transparency.
[0006] On the other hand, the titanium oxide organosol is put down in writing in the patent documentation 4, which contains: rutile titanium oxide particles, silane coupling agents, alkaline additives and non-water-soluble organic solvents that have been surface-treated by the hydrated oxides of tin etc. And it is put down in writing: the modulation is coated with after the dispersion liquid that has further added UV curing resin in this organosol, the non-water-soluble organic solvent is evaporated, and then ultraviolet irradiation is carried out, thereby forming a film of high refractive index and high hardness, which is suitable for optical element. However, a large amount of non-water-soluble organic solvents are mixed in the dispersion liquid that the patent documentation 4 is put down in writing. And even if the film is completed, the solvent residual rate is also high, which is not suitable for the sealing material used as electronic devices.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent document 1: WO2017 / 170888A1;
[0010] Patent document 2: WO2013 / 005441A1;
[0011] Patent document 3: Japanese Patent Application Publication No. 2020-26515;
[0012] Patent document 4: WO2021 / 193262A1. Summary of the invention
[0013] Problems to be solved by the invention
[0014] The present invention is made to solve the above-mentioned problems, and its purpose is to provide a dispersion liquid and a method for producing the same, wherein the dispersion liquid contains titanium oxide particles, has a high refractive index, is excellent in transparency, has a low content of volatile solvents, and has a low viscosity and excellent viscosity stability. In addition, the present invention also aims to provide a sealant composed of the dispersion liquid; and to provide a cured product obtained by curing the dispersion liquid and its use.
[0015] Means for solving problems
[0016] The above-mentioned problems are solved by providing a dispersion liquid, which is a dispersion liquid containing titanium oxide particles, a silane coupling agent and a monomer having a polymerizable functional group;
[0017] The titanium oxide particles are particles obtained by surface treating a core of rutile titanium oxide with a hydrous oxide of tin or zirconium. The titanium oxide content in the particles is 1.3477 W / m2 TiO 2 The content of the hydrated oxide of tin or zirconium is 70 to 95% by mass as SnO 2 or ZrO 2 5 to 30% by mass
[0018] The viscosity of the above monomer at 25°C is 100 mPa·s or less,
[0019] The dispersion was strongly heated at 925°C for 2 hours to obtain a solid content of 15 to 55% by mass.
[0020] In the dispersion, the content of the silane coupling agent is 2 to 15% by mass, the content of the monomer is 30 to 85% by mass, the content of the organic solvent having no polymerizable functional group is 10% by mass or less, and
[0021] The viscosity of the dispersion at 25° C. is 500 mPa·s or less.
[0022] In this case, it is preferred that the wet specific surface area of the titanium oxide particles measured by pulse NMR is 20 to 150 m 2 / g. It is also preferred that the titanium oxide particles are particles that have been debonded using an alkaline additive. It is also preferred that the average particle size of the titanium oxide particles in a liquid having a solid content of 5% by weight obtained by diluting the dispersion with the monomer is 20 to 50 nm. It is also preferred that the haze of a liquid having a solid content of 5% by weight obtained by diluting the dispersion with the monomer is 40% or less at an optical path length of 10 mm.
[0023] A preferred embodiment is a curable sealing material composed of the above-mentioned dispersion. In this case, it is more preferably a sealing material for sealing an optical element. In addition, a cured product formed by curing the above-mentioned dispersion is also a preferred embodiment of the present invention. In this case, it is preferred that the refractive index of the cured product at 20°C and 633nm is 1.6 or more. In addition, it is also preferred that the residual rate of the organic solvent in the cured product is 0.1 to 10% by mass. Moreover, an optical element sealed with the above-mentioned cured product is also a preferred embodiment.
[0024] The above-mentioned problem is also solved by providing a method for producing the above-mentioned dispersion, wherein water is removed from the aqueous dispersion of the above-mentioned titanium oxide particles and replaced with the above-mentioned organic solvent, the above-mentioned silane coupling agent is added to the obtained dispersion, and then the organic solvent is removed and replaced with the above-mentioned monomer. In this case, it is preferred that the above-mentioned silane coupling agent and the alkaline additive are added to the dispersion replaced with the above-mentioned organic solvent to dissolve the above-mentioned titanium oxide particles, and then the organic solvent is removed and replaced with the above-mentioned monomer.
[0025] Effects of the Invention
[0026] The dispersion of the present invention contains titanium oxide particles, has a high refractive index, excellent transparency, a low content of volatile solvents, and is low in viscosity and excellent in viscosity stability. The dispersion can be easily cured by ultraviolet irradiation or the like, and is suitable as a sealant for electronic devices, etc., especially a sealant for optical elements. In addition, according to the production method of the present invention, such a dispersion can be obtained. DETAILED DESCRIPTION
[0027] The dispersion of the present invention is a dispersion containing surface-treated titanium oxide particles, a silane coupling agent, and a monomer having a polymerizable functional group. The dispersion will be described below.
[0028] The titanium oxide particles contained in the dispersion of the present invention are particles formed by surface treating the core of rutile titanium oxide with a hydrated oxide of tin or zirconium. The titanium oxide contained in the particles has a rutile crystal form. Thus, the refractive index is improved, and the photocatalytic activity is reduced, so it is not easy to cause adverse effects on electronic devices when used in a sealant. The hydrated oxide of tin or zirconium present on the core surface of titanium oxide has a high affinity with a silane coupling agent or an alkaline additive, so it helps to stably disperse the titanium oxide particles in the dispersion medium. In addition, the viscosity of the dispersion can be suppressed from rising over time, and a dispersion with high viscosity stability can be obtained. Moreover, the hydrated oxide of tin or zirconium has a higher refractive index, so the reduction in refractive index caused by surface treatment can be suppressed.
[0029] The content of titanium oxide in the particles is expressed as TiO 2 The content of the hydrated oxide of tin or zirconium is 70 to 95% by mass as SnO 2 or ZrO 2 The content of titanium oxide is preferably 5 to 30% by mass. By making the content of titanium oxide 70% by mass or more, a dispersion with a high refractive index can be obtained. The content of titanium oxide is preferably 75% by mass or more, more preferably 80% by mass or more. At this time, the content of the hydrated oxide of tin or zirconium is preferably 25% by mass or less, more preferably 20% by mass or less. In addition, by making the content of the hydrated oxide of tin or zirconium 5% by mass or more, the viscosity stability of the dispersion of the present invention becomes good, and the transparency also becomes good. The content of the hydrated oxide of tin or zirconium is preferably 7% by mass or more, more preferably 8% by mass or more. At this time, the content of titanium oxide is preferably 93% by mass or less, more preferably 92% by mass or less. It should be noted that the content here refers to the percentage when all the oxides or hydrated oxides of the metal or silicon contained in the particles are converted into oxides and the total mass is set to 100.
[0030] The wet specific surface area of the titanium oxide particles measured by pulse NMR is preferably 20 to 150 m 2When the wet specific surface area is too large, the time stability of the viscosity of the dispersion decreases, and the viscosity may increase during storage. The wet specific surface area is more preferably 120 m 2 / g or less. The wet specific surface area is less than 20m 2 When the average particle size is 0.17777 Å / g, the average particle size becomes large, the haze becomes high, and sufficient transparency may not be obtained.
[0031] The calcined solid content when the dispersion of the present invention is calcined at 925°C for 2 hours is preferably 15 to 55% by mass. By making the calcined solid content 15% or more by mass, the refractive index of the dispersion is improved. The calcined solid content is more preferably 20% or more by mass, and further preferably 25% or more by mass. On the other hand, by making the calcined solid content 55% or less by mass, the viscosity of the dispersion can be reduced. The calcined solid content can be 50% or less by mass, or 45% or less by mass, or 40% or less by mass, or 35% or less by mass. Here, the calcined solid content refers to the ash obtained by heating the dispersion of the sample at 925°C in the atmosphere for 2 hours to completely oxidize the metal component and the silicon component.
[0032] The TiO in the calcined solid content obtained by calcining the dispersion of the present invention at 925°C for 2 hours is preferably 2 The content of TiO is 70 to 95% by mass. 2 When the content of TiO is 70% by mass or more, a dispersion with a high refractive index can be obtained. 2 The content of TiO is more preferably 75% by mass or more, and further preferably 80% by mass or more. On the other hand, from the viewpoint of the viscosity stability and transparency of the dispersion, TiO 2 The content of is preferably 95 mass % or less.
[0033] The dispersion of the present invention contains a silane coupling agent. By containing the silane coupling agent, the dispersibility of the titanium oxide particles becomes good, and a dispersion having excellent transparency and viscosity stability can be obtained. As the silane coupling agent, known substances can be used, and examples thereof include vinyl trimethoxysilane, vinyl triethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, p-phenylene trimethoxysilane, 3-acryloxypropyl trimethoxysilane, 3-methacryloxypropyl methyl dimethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-methacryloxypropyl methyl diethoxysilane, 3-methacryloxypropyl triethoxysilane, tris-(trimethoxysilylpropyl) isocyanurate, 3-ureidopropyl trialkoxysilane, 3-mercaptopropyl methyl dimethoxysilane, 3-mercaptopropyl trimethoxysilane, and the like. Among them, considering the affinity or reactivity with the monomer used as the dispersion medium, a substance having a polymerizable functional group is preferred, preferably a substance having a polymerizable double bond such as a (meth) acrylic group ((meth) acrylic acid type group) or a vinyl group. Among them, a silane coupling agent containing a (meth) acrylic group with good polymerizability is preferred, and examples thereof include 3-acryloxypropyltrimethoxysilane or 3-methacryloxypropyltrimethoxysilane.
[0034] The content of the silane coupling agent in the dispersion of the present invention is 2 to 15% by mass. By making the content of the silane coupling agent 2% or more by mass, the above-mentioned addition effect can be exerted. The content of the silane coupling agent is preferably 4% or more by mass, more preferably 5% or more by mass, and further preferably 6% or more by mass. On the other hand, if the silane coupling agent is too much, the refractive index is reduced. The content of the silane coupling agent is preferably 12% or less by mass, more preferably 10% or less by mass. It should be noted that the silane coupling agent can be bonded to the surface of the titanium oxide particles, or a portion of the alkoxy groups contained in the silane coupling agent can be hydrolyzed.
[0035] The dispersion medium in the dispersion of the present invention is a monomer having a polymerizable functional group. By dispersing titanium oxide particles in such a monomer, a polymerization reaction can be carried out to make the dispersion easily solidified. The monomer used here is not limited to its type as long as it has a polymerizable functional group. A monomer having a polymerizable double bond that can be addition polymerized or a monomer having an epoxy group that can be ring-opening polymerized can be used. From the perspective of being easily solidified by ultraviolet rays, etc., a monomer having a polymerizable double bond such as a (meth) acrylic group or a vinyl group is preferred. Among them, a monomer containing a (meth) acrylic group with good polymerizability is preferred. If the number of (meth) acrylic groups in one molecule of monomer is too much, the viscosity becomes high, so the number is preferably 1 to 3, and more preferably 1 to 2. Here, when multiple monomers are used, it is sufficient as long as the simple average value is included in the above range.
[0036] Specific examples of the monomer containing a (meth)acrylic group include benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, n-octyl (meth)acrylate, diphenyl methyl (meth)acrylate, phenoxybenzyl (meth)acrylate, ethoxylated phenyl (meth)acrylate, tripropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, naphthyl methyl (meth)acrylate, and dimethyl (meth)acrylamide.
[0037] In addition, the viscosity of the monomer used in the present invention at 25°C is 100 mPa·s or less. By using such a low-viscosity monomer, the viscosity of the obtained dispersion is also reduced, providing a dispersion with excellent fluidity. The viscosity of the monomer is preferably 50 mPa·s or less, more preferably 30 mPa·s or less. On the other hand, the viscosity of the monomer is usually 1 mPa·s or more. Here, when multiple monomers are used, it is sufficient as long as the viscosity of their mixture is included in the above range.
[0038] The refractive index of the monomer used in the present invention at 20°C and 589nm is preferably 1.45 or more, more preferably 1.5 or more, and further preferably 1.55 or more. On the other hand, the refractive index of the monomer is usually 1.7 or less. Here, when multiple monomers are used, as long as the refractive index of their mixture is within the above range. In order to increase the refractive index, it is preferred to use a monomer having an aromatic ring in the molecule.
[0039] The content of the above-mentioned monomer in the dispersion of the present invention is 30 to 85% by mass. By making the content of the monomer 30% or more, a low-viscosity dispersion can be prepared. The content of the monomer can be 35% or more by mass, 40% or more by mass, 45% or more by mass, 50% or more by mass, or 55% or more by mass. On the other hand, if there are too many monomers, the refractive index cannot be increased. The content of the monomer is preferably 80% or less by mass, more preferably 75% or less by mass.
[0040] The content of the organic solvent without a polymerizable functional group in the dispersion of the present invention is 10% by mass or less. Therefore, the organic solvent is included in the dispersion of the present invention as an optional component. As the organic solvent, it is suitable to use a solvent that is miscible with the monomer and has a lower boiling point than the monomer. Ketones, esters, ethers, alcohols, etc. can be used. Specifically, butanone, acetone, methyl acetate, ethyl acetate, diethyl ether, tetrahydrofuran, methanol, ethanol, propanol, isopropanol, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, etc. can be used. Considering the safety of the operation or the impact on the working environment, the boiling point of the organic solvent is preferably above 40°C, more preferably above 50°C, and more preferably above 60°C. On the other hand, considering the efficiency of the organic solvent being replaced by the monomer, the boiling point of the organic solvent is preferably below 150°C, more preferably below 120°C, and more preferably below 100°C. In addition, the boiling point difference between the organic solvent and the monomer is preferably 80°C or more, but even if there is no boiling point difference, it does not hinder the replacement of the monomer.
[0041] By making the content of this organic solvent be below 10 mass %, the volatilization of organic solvent to the surrounding environment can be suppressed when coating or filling. In addition, even if solidified in the state of taking in a small amount of organic solvent, if the organic solvent is non-volatile, then there is often no problem. The content of organic solvent is preferably below 8 mass %, more preferably below 6 mass %. On the other hand, the less the content of organic solvent, the more good the organic solvent is non-volatile, but the usage amount of the monomer used for replacement is too much or the energy required for replacement is too much and uneconomical, and the stability over time of dispersion liquid is also likely to deteriorate. The content of organic solvent in the dispersion liquid of the present invention can be more than 0.1 mass %, can also be more than 0.5 mass %, can also be more than 1 mass %.
[0042] The method for producing the dispersion of the present invention is described below. A preferred method for producing the dispersion is as follows: water is removed from an aqueous dispersion of titanium oxide particles and replaced with an organic solvent, a silane coupling agent is added to the obtained dispersion, and then the organic solvent is removed and replaced with the above-mentioned monomer.
[0043] First, the steps for preparing an aqueous dispersion of titanium oxide particles are described. The method for preparing the aqueous dispersion is not particularly limited, and a known method can be used. Examples include: a method in which a water-soluble tin compound (rutile agent) and a water-soluble titanium compound are dissolved in water for hydrolysis, and after removing salts, an acid or alkali is mixed for degumming; or a method in which a water-soluble tin compound is dissolved in water for heating and hydrolysis, thereby precipitating a portion of the water-soluble tin compound, and then a water-soluble titanium compound is added for hydrolysis, and after removing salts, an acid or alkali is mixed for degumming, etc.
[0044] Examples of water-soluble titanium compounds include titanium oxysulfate, titanium tetrachloride, titanium sulfate, and the like. Examples of water-soluble tin compounds (rutile agents) include tin sulfate, tin chloride, tin nitrate, and the like. In addition, examples of acids include hydrochloric acid, nitric acid, oxalic acid, and the like. Examples of alkalis include sodium hydroxide or amines such as tert-butylamine, isopropylamine, diethylamine, and triethanolamine. The amount of tin compound added is 100 parts by mass of titanium oxide (TiO 2 Conversion), SnO 2 The amount is usually 1 to 25 parts by mass, preferably 1 to 10 parts by mass.
[0045] As a specific method for the above steps, for example, the following method can be exemplified. First, titanyl sulfate and a small amount of tin sulfate are dissolved in water. The tin compound added at this time is a rutile agent for making the crystal form of the obtained titanium oxide particles rutile. Next, the obtained aqueous solution is neutralized with an alkali to precipitate a mixture of hydrated titanium oxide and hydrated tin oxide. After filtering and washing the mixture to obtain a filter cake, hydrochloric acid is added, and the filter cake is degummed while stirring, thereby obtaining an aqueous dispersion of rutile titanium oxide particles.
[0046] Next, the obtained titanium oxide particles are subjected to surface treatment. There is no particular limitation on the method for performing the surface treatment, and known methods may be used. Examples include: a method of adding a water-soluble compound of tin or zirconium to the aqueous dispersion of the rutile titanium oxide particles obtained as above, and then adjusting the pH with an acid or a base; or a method of adding a water-soluble compound of tin or zirconium while adjusting the pH of the aqueous dispersion of the rutile titanium oxide particles with an acid or a base, etc. Thus, the core of the rutile titanium oxide is covered with a hydrated oxide of tin or zirconium and subjected to surface treatment. At this time, the content of the hydrated oxide of tin or zirconium in the titanium oxide particles is expressed as SnO 2 or ZrO 2 The conversion is 5 to 30% by mass. Next, the precipitate is filtered and washed as needed, and water is added again to obtain an aqueous suspension of rutile titanium oxide particles surface-treated with a hydrous oxide of tin or zirconium. In the aqueous suspension obtained by the above operation, the surface-treated titanium oxide particles aggregate and become turbid.
[0047] Next, the dispersion medium of the aqueous suspension of the surface-treated rutile titanium oxide particles obtained by the above steps is replaced with an organic solvent. Water-soluble organic solvents such as alcohols such as methanol, ethanol, and isopropanol, ketones such as acetone, and ethers such as tetrahydrofuran can be used. After adding a water-soluble organic solvent to the aqueous suspension of titanium oxide particles, the solvent can be replaced with these water-soluble organic solvents by ultrafiltration, dialysis, evaporation, and other methods. Afterwards, the dispersion medium can be further replaced with a non-water-soluble organic solvent as needed. As non-water-soluble organic solvents, examples include: ketones such as butanone and methyl isobutyl ketone; esters such as methyl acetate and ethyl acetate; ethers such as diethyl ether. The non-water-soluble organic solvent has good affinity with the monomer to be replaced later, so the operation of replacing the monomer becomes easy. It should be noted that here, the water-soluble organic solvent is a solvent that can be mixed with water at a free ratio, and the non-water-soluble organic solvent is an organic solvent other than it.
[0048] By adding a silane coupling agent to the suspension in which titanium oxide particles are dispersed in an organic solvent obtained in this way and mixing them, a dispersion in which the titanium oxide particles are debonded and finely dispersed in the organic solvent can be obtained. At this time, an amine or a dispersant having an amine value is further added as an alkaline additive, so that the debonding can be more effective. As amines that can be used as alkaline additives, examples include: alkylamines such as tert-butylamine, isopropylamine, diisopropylamine, diethylamine, propylamine, n-butylamine, and isobutylamine; alkanolamines such as triethanolamine, diethanolamine, N-methylethanolamine, and 2-amino-2-methyl-1-propanol; heterocyclic amines such as pyridine. In addition, as dispersants with amine values that can be used as alkaline additives, examples include: dispersants such as DISPERBYK-108, DISPERBYK-109, and DISPERBYK-180 (manufactured by BYK Chemie Co., Ltd., Japan). Relative to 100 parts by mass (TiO 2 The amount of the alkaline additive added is preferably 1 to 20 parts by mass. When the boiling point of the alkaline additive is low, most of it is removed from the dispersion by the subsequent replacement operation. When used as a sealing material for electronic devices, it is sometimes preferable that no alkaline additive remains in the dispersion. In this case, it is preferred to use an alkaline additive with a low boiling point. As a preferred boiling point, it is the same as the boiling point of the above-mentioned organic solvent that does not have a polymerizable functional group. It should be noted that in order to further improve the dispersion stability of the titanium oxide particles in the dispersion, a dispersant that is not an alkaline additive (i.e., a dispersant that does not have an amine value) may be added.
[0049] The dispersion medium of the dispersion obtained by the above steps is replaced by a monomer having a polymerizable functional group. There is no particular limitation on the replacement method, and ultrafiltration, dialysis, evaporation and the like can be used. Among them, evaporation is preferred from the perspective of simplicity and low cost. While appropriately adding monomers, evaporation is performed and concentrated to an appropriate concentration to obtain the dispersion of the present invention. Alternatively, the dispersion medium can be concentrated to 3 to 10% by mass for solidification, and then replaced by adding monomers. In this case, it is preferably crushed with a bead mill or the like after replacement.
[0050] The dispersion of the present invention has good transparency. Specifically, the haze of a liquid having a solid content of 5% by weight obtained by diluting the dispersion with the above-mentioned monomer at an optical path length of 10 mm is preferably 40% or less. The haze is more preferably 35% or less, and further preferably 30% or less.
[0051] In addition, the average particle size of the titanium oxide particles in a liquid having a solid content of 5% by weight obtained by diluting the dispersion of the present invention with a monomer used as a dispersion medium is preferably 20 to 50 nm. By making the average particle size 50 nm or less, a dispersion having excellent transparency can be obtained. The average particle size is more preferably 45 nm or less.
[0052] The viscosity of the dispersion of the present invention at 25°C is 500mPa·s or less. By making the viscosity of the dispersion low, it is easy to apply when used as a sealing material. For example, an inkjet printer can be used to apply only to necessary parts, and it is also easy to follow the unevenness. Moreover, when filled between an electronic device and a cover member, it can also be easily and uniformly filled in a narrow gap. The viscosity of the dispersion is preferably 300mPa·s or less, more preferably 200mPa·s or less, and further preferably 100mPa·s or less.
[0053] There is no particular limitation on the method for curing the dispersion of the present invention. It can be cured by heating, or by irradiating ultraviolet rays or electron beams. Preferably, a polymerization initiator is mixed before curing, and then heated or irradiated with ultraviolet rays. As the type of polymerization initiator, free radical polymerization initiator, ion polymerization initiator, photopolymerization initiator, etc. can be listed. In the case of being used as a sealing material for electronic devices, it is advisable to avoid heating, so a photopolymerization initiator is preferably used. Specifically, 1-hydroxycyclohexyl phenyl ketone, bis (2,4,6-trimethylbenzoyl) -phenyl phosphine oxide, 3-hydroxybenzophenone, 2,2-dimethoxy-2-phenyl acetophenone, 2-methyl-1-[4-(methylthio) phenyl] -2-morpholinopropane-1-one, monoacylphosphine oxide, 4,4'-bis (dimethylamino) benzophenone, 2,4-diethylthioxanthone, etc., these polymerization initiators can also be used in one or mixed with two or more.
[0054] When the dispersion of the present invention is filled in a narrow space and solidified, the organic solvent residual rate (mass %) of the solidified product is not different from the organic solvent content (mass %) of the dispersion. Therefore, the preferred range of the organic solvent residual rate of the solidified product in this case is the same as the preferred range of the organic solvent content of the dispersion of the present invention.
[0055] The refractive index of the dispersion of the present invention at 20°C and 633nm is preferably 1.55 or more. Thus, a cured product with a high refractive index can be obtained. The refractive index of the dispersion is more preferably 1.6 or more, and further preferably 1.65 or more. In addition, the cured product obtained by curing the dispersion of the present invention preferably has a refractive index of 1.6 or more at 20°C and 633nm. The refractive index is more preferably 1.65 or more, and further preferably 1.7 or more. By obtaining a cured product with a high refractive index, when used as a sealing material for an electronic device, the refractive index difference between the high refractive index component constituting the device and the sealing material can be reduced, and the light loss caused by reflection or refraction can be reduced.
[0056] The preferred application of the dispersion of the present invention is a sealing material. In order to protect electronic devices from the influence of oxygen or moisture, the sealing material of the present invention is cured after coating or filling, thereby protecting the electronic devices. In particular, in applications where light from optical elements such as organic EL elements, liquid crystal elements, and LED elements passes through the sealing material, it is suitable to use the dispersion of the present invention having a high refractive index and high transparency.
[0057] Among them, useful is a sealing material for sealing an organic EL element. Organic EL elements are easily degraded by oxygen or moisture, and it is important to protect them with a sealing material. The sealing material of the present invention has a low viscosity, so when the sealing material is applied to the organic EL element, an inkjet printer or the like can be used to apply it only to the necessary parts, and it can also easily follow the unevenness. In addition, even when the sealing material is filled between the organic EL element and the cover member, the sealing material of the present invention has a low viscosity, so it can also be easily and evenly filled in a narrow gap.
[0058] Example
[0059] Hereinafter, the present invention will be described in more detail by way of examples.
[0060] Example 1
[0061] (Step A: Preparation of Aqueous Dispersion of Titanium Oxide Particles)
[0062] Titanyl sulfate dihydrate (TiOSO 4 ·2H 2 O) 303g TM crystals (TiO 2 100 g) and 4.3 g tin sulfate (SnSO4 )(SnO 2 3.0 g: relative to 100 parts by mass of TiO 2 3 parts by mass) was dissolved in 1692.7 g of water. Next, the obtained aqueous solution was adjusted to pH 7.0 using a 10% by mass sodium hydroxide aqueous solution to precipitate a mixture of hydrated titanium oxide and hydrated tin oxide. Afterwards, the mixture was filtered and washed with water to obtain a filter cake with a solid content of 11.0% by mass. 278 g of concentrated hydrochloric acid (100 g in terms of HCl) and 785.6 g of water were slowly added to 936.4 g of the filter cake, and the filter cake was degummed while stirring, thereby obtaining an aqueous dispersion of 2000 g of rutile titanium oxide particles (TiO 2 The concentration is 5 mass %). (Step B: Surface treatment of titanium oxide particles)
[0063] 14.3 g of tin sulfate (SnSO) was added to the 2000 g aqueous dispersion of rutile titanium oxide particles obtained in step A. 4 )(SnO 2 10.0 g: relative to 100 parts by mass of TiO 2 Next, the obtained aqueous dispersion was adjusted to pH 6.0 using a 10% by mass sodium hydroxide aqueous solution, so that the hydrous oxide of tin was precipitated on the surface of the core composed of titanium oxide particles to perform surface treatment. Next, the precipitate was filtered and washed, and water was added to adjust the concentration to obtain a precipitate of 10 parts by mass (SnO 2 tin oxide hydrous oxide to 100 parts by mass (TiO 2 1000 g of an aqueous suspension of rutile titanium oxide particles (TiO 2 The concentration is 10% by mass).
[0064] (Step C: replacing the dispersion medium from water to an organic solvent)
[0065] 1000 g of isopropanol and 1000 g of butanone were added to the aqueous suspension of 1000 g of titanium oxide particles obtained in step B. Then, while further adding butanone, ultrafiltration was performed to replace the dispersion medium with butanone, and a total amount of 1000 g (TiO 2 Next, 25 g of 3-acryloxypropyltrimethoxysilane (100 parts by mass of TiO2) as a silane coupling agent was added. 2 25 parts by mass) and 5 g of tert-butylamine as a basic additive (relative to 100 parts by mass of TiO 2 5 parts by mass), and 1030 g of a methyl ethyl ketone dispersion of surface-treated rutile titanium oxide particles was obtained.
[0066] (Step D: Replacing the dispersion medium from an organic solvent to a monomer)
[0067] 500 g of benzyl acrylate (refractive index of 1.52 at 20°C and 589 nm; viscosity of 3 mPa·s at 25°C) as a monomer having a polymerizable functional group was added to 1030 g of the butanone dispersion obtained in step C. Benzyl acrylate was then added and concentrated using an evaporator to replace butanone with benzyl acrylate. After concentrating to 313 g, a dispersion treatment was performed using a bead mill to obtain a dispersion of surface-treated rutile titanium oxide particles.
[0068] (Evaluation of dispersion)
[0069] The content of butanone in the dispersion obtained in this way was 4.6% by mass. Here, the content of the solvent (butanone) in the dispersion was obtained by preparing a calibration curve of butanone using a gas chromatograph "GASCHROMATOGRAPH GC-14B" manufactured by Shimadzu Corporation, and then quantifying the content of butanone (mass %) in the dispersion.
[0070] The calcined solid content of the dispersion was 31.4% by mass when calcined at 925°C. 2 The content of was 26.3% by mass. Here, the calcined solid content was calculated by measuring the mass (h) of the solid content after heating at 925° C. for 2 hours after a certain amount (W) of the dispersion of about 1 g was placed in a crucible.
[0071] Ignition solid content (mass %) = (h / W) × 100
[0072] In addition, TiO 2 The solid content was analyzed using a fluorescent X-ray analyzer "SUPERMINI" manufactured by Rigaku Co., Ltd. to determine the TiO content in the dispersion. 2 Content (mass %).
[0073] According to the above analysis results, 313 g of the dispersion contained 26.3 mass % (82.3 g) of TiO 2 , 3.4 mass% (10.7 g) SnO 2 , 8.0 mass % (25 g) of 3-acryloxypropyltrimethoxysilane as a silane coupling agent, and 4.6 mass % (14.4 g) of butanone as an organic solvent. Thus, it can be calculated that the remaining 58 mass % (181 g) is benzyl acrylate as a monomer. It should be noted that, as shown in the filler ratio, it is estimated that relative to 100 parts by mass of TiO 2 Contains 13 parts by mass of SnO 2It is assumed that the silane coupling agent does not volatilize and is not hydrolyzed. In addition, it is assumed that isopropyl alcohol is replaced by methyl ethyl ketone and does not remain, and tert-butylamine (boiling point 45.5° C.) volatilizes and does not remain.
[0074] The viscosity of the dispersion immediately after manufacture was 12 mPa·s. In addition, the viscosity after a 2-week time test at 40°C was 14 mPa·s, and a 17% increase in viscosity was observed. Here, the viscosity of the dispersion is the viscosity (mPa·s) measured at 25°C and a rotation speed of 60 rpm using an E-type viscometer. The viscosity of the dispersion after time was measured in the same manner at 25°C after standing in a constant temperature bath at 40°C for 2 weeks.
[0075] The haze value of the liquid obtained by diluting the above-mentioned solid content on burning with a monomer to 5% by mass under an optical path of 10 mm is 28%. The method for measuring the haze value at this time is as follows. The monomer used when making the dispersion is used to dilute the dispersion so that the solid content on burning is 5% by mass. The dilution is placed in a quartz cell with an optical path of 10 mm, and the haze meter "NDH 4000" manufactured by Nippon Denshoku Industries Co., Ltd. is used to measure the haze value (%) of the dispersion.
[0076] The average particle size in the liquid obtained by diluting the above-mentioned solid content on burning with a monomer to 5% by mass is 36nm. The method for measuring the average particle size at this time is as follows. The monomer used when making the dispersion is used to dilute the dispersion so that the solid content on burning is 5% by mass. The particle size distribution of the dilution is measured using the "Zeta-Potential & Particle size Analyzer ELSZ-1000" manufactured by Otsuka Electronics Co., Ltd., and D50 (median diameter) is used as the average particle size (nm).
[0077] The wet specific surface area of the particles in the monomer dispersion is 45 m 2 Here, the wet specific surface area is the wet specific surface area (m2) of particles dispersed in a monomer measured using an NMR wet specific surface area measuring device "Acorn Area" manufactured by Xigo nanotools, USA. 2 / g).
[0078] (Formation of coating film)
[0079] To the dispersion of titanium oxide particles thus obtained, 0.3 g of 1-hydroxycyclohexyl phenyl ketone and 0.3 g of bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide as polymerization initiators were added and stirred for 1 hour. The dispersion thus obtained was spin-coated on a micro-slide plate (70×55×1.3 mm) manufactured by Matsunami Glass Industries Co., Ltd. at 25°C, 50% humidity, 1000 rpm, and 3 seconds. After standing at 25°C for 30 minutes, the plate was irradiated with 580 mJ / cm 2 The ultraviolet rays cured it to form a coating with a thickness of 1 μm.
[0080] (Evaluation of coating film)
[0081] The refractive index of the coating before curing is 1.69, and the refractive index of the coating after curing is 1.71. Here, the refractive index of the coating is obtained by measuring the refractive index of the coating sample formed on the glass plate at 20°C and 633nm using an ellipsometer (Ellipsometer) "DVA-FL3G" manufactured by Mizojiri Optical Research Institute Co., Ltd. The haze in the cured coating is 0.10%. The haze value (%) of these coatings is a coating with a film thickness of about 1 μm on a glass plate measured using a haze meter "NDH 4000" manufactured by Nippon Denshoku Industries Co., Ltd. In addition, the solvent residual rate of the cured coating is 0.5% by mass. Here, the solvent residual rate of the cured coating is to peel off the cured coating from the glass plate, use a thermogravimetric / differential thermal analyzer "TG-DTA7300" manufactured by Hitachi High-TechScience Co., Ltd., heat up at a rate of 5°C / minute, and obtain the solvent residual rate (mass %) from the weight reduction rate at 100°C. The above results are summarized and shown in Tables 1 to 3 together with the results of other Examples or Comparative Examples.
[0082] Example 2
[0083] In step D, except that phenoxyethyl acrylate was used as the monomer and the concentration was performed to 341 g, the same operation as in Example 1 was carried out to obtain a dispersion in which the surface-treated rutile titanium oxide particles were dispersed in the monomer, and then a coating film was formed.
[0084] Example 3
[0085] In addition to changing the amount of tin sulfate added in step B to 7.1 g (in terms of SnO 2 5.0 g: relative to 100 parts by mass of TiO 2 The same operation as in Example 1 was performed except that n-octyl acrylate was used as the monomer in step D and the concentration was performed to 327 g to obtain a dispersion in which surface-treated rutile titanium oxide particles were dispersed in the monomer, and a coating film was formed.
[0086] Example 4
[0087] In addition to using 3-methacryloxypropylmethoxysilane as the silane coupling agent in step C, the amount of the silane coupling agent added was 100 parts by mass of TiO 2 The same operation as in Example 1 was carried out except that the amount was changed to 30 parts by mass and biphenyl methyl acrylate was used as the monomer in step D and the concentration was performed to 481 g to obtain a dispersion in which surface-treated rutile titanium oxide particles were dispersed in the monomer, and then a coating film was formed.
[0088] Example 5
[0089] The same operation as in Example 1 was carried out except that 3-methacryloxypropylmethoxysilane was used as a silane coupling agent in step C, phenoxybenzyl acrylate was used as a monomer in step D, and the concentration was performed to 397 g to obtain a dispersion in which surface-treated rutile titanium oxide particles were dispersed in the monomer, and then a coating film was formed.
[0090] Example 6
[0091] In addition to using 3-methacryloxypropylethoxysilane as the silane coupling agent in step C, the amount of the silane coupling agent added was 100 parts by mass of TiO 2 The same operation as in Example 1 was carried out except that the amount was changed to 20 parts by mass and ethoxylated phenyl acrylate was used as the monomer in step D and the concentration was performed to 390 g to obtain a dispersion in which surface-treated rutile titanium oxide particles were dispersed in the monomer, and then a coating film was formed.
[0092] Example 7
[0093] The same operation as in Example 1 was carried out except that 3-methacryloxypropylethoxysilane was used as a silane coupling agent in step C, ethoxylated phenyl acrylate was used as a monomer in step D, and concentration was performed to 394 g to obtain a dispersion in which surface-treated rutile titanium oxide particles were dispersed in the monomer, and then a coating film was formed.
[0094] Example 8
[0095] In addition to changing the amount of tin sulfate added in step B to 42.9 g (in terms of SnO 2 30 g: relative to 100 parts by mass of TiO 2 The same operation as in Example 1 was performed except that the monomer was 30 parts by mass), tripropylene glycol diacrylate was used as the monomer in step D, and the concentration was performed to 465 g to obtain a dispersion in which surface-treated rutile titanium oxide particles were dispersed in the monomer, and a coating film was formed.
[0096] Example 9
[0097] A coating film was formed in the same manner as in Example 1 except that trimethylolpropane triacrylate was used as the monomer and the concentration was performed to 597 g. A dispersion in which surface-treated rutile titanium oxide particles were dispersed in the monomer was obtained.
[0098] Example 10
[0099] A coating film was formed in the same manner as in Example 1 except that trifluoropropyltrimethoxysilane was used as a silane coupling agent in step C, naphthyl methyl acrylate was used as a monomer in step D, and concentration was performed to 480 g.
[0100] Embodiment 11
[0101] A coating film was formed in the same manner as in Example 1 except that trifluoropropyltrimethoxysilane was used as a silane coupling agent in step C and concentration was performed to 343 g in step D to obtain a dispersion in which surface-treated rutile titanium oxide particles were dispersed in a monomer.
[0102] Example 12
[0103] In step B, 13.1 g of zirconium oxychloride octahydrate (ZrO 2 5 g: relative to 100 parts by mass of TiO 2 5 parts by mass), and adjusted to pH 6.0 using a 10% by mass aqueous sodium hydroxide solution. Next, 14.3 g of tin sulfate (SnO 2 10.0 g: relative to 100 parts by mass of TiO 2 10 parts by mass) was added, and the pH was adjusted to 6.0 using a 10% by mass sodium hydroxide aqueous solution. In this way, hydrated oxides of zirconium and tin were precipitated on the surface of the core composed of titanium oxide particles to perform surface treatment. Next, the precipitate was filtered and washed, and water was added to adjust the concentration to obtain a 5 parts by mass (ZrO 2 10 parts by mass of zirconium hydrate oxide and 10 parts by mass of SnO 2 tin oxide hydrous oxide to 100 parts by mass (TiO 2 1000 g of an aqueous suspension of titanium oxide particles (TiO 2The concentration was 10% by mass). In step D, naphthyl methyl acrylate was used as a monomer and the concentration was carried out to 498 g. Except for these points, the same operation as in Example 1 was carried out to obtain a dispersion in which surface-treated rutile titanium oxide particles were dispersed in the monomer, and then a coating film was formed.
[0104] Embodiment 13
[0105] In step B, 17.2 g of sodium silicate No. 3 (SiO 2 Concentration is 29 mass %) (SiO 2 5 g: relative to 100 parts by mass of TiO 2 Next, 14.3 g of tin sulfate (SnO 2 10.0 g: relative to 100 parts by mass of TiO 2 After 5 parts by mass (SiO 2 ), a 10% by mass aqueous solution of sodium hydroxide was used to adjust the pH to 6.0. In this way, hydrated oxides of silicon and tin were precipitated on the surface of the core composed of titanium oxide particles to perform surface treatment. Next, the precipitate was filtered and washed, and water was added to adjust the concentration to obtain a 5 parts by mass (SiO 2 ) core. 2 10 parts by mass of hydrated oxide of silicon (SnO 2 tin oxide hydrous oxide to 100 parts by mass (TiO 2 1000 g of an aqueous suspension of titanium oxide particles (TiO 2 The concentration was 10% by mass). In step D, the concentration was performed to 355 g. Except for these points, the same operation as in Example 1 was carried out to obtain a dispersion in which surface-treated rutile titanium oxide particles were dispersed in a monomer, and then a coating film was formed.
[0106] Embodiment 14
[0107] In addition to adding tert-butylamine as a basic additive in step C, a dispersant (5 g of "DISPERBYK-111" manufactured by BYK Chemie Co., Ltd., Japan: 5 g per 100 parts by mass of TiO 2 The same operation as in Example 1 was performed except that the monomer was 5 parts by mass), and trimethylolpropane triacrylate was used as the monomer in step D and the concentration was performed to 498 g to obtain a dispersion in which the surface-treated rutile titanium oxide particles were dispersed in the monomer, and then a coating film was formed. It should be noted that DISPERBYK-111 is a dispersant having no amine value (i.e., an amine value of zero).
[0108] Embodiment 15
[0109] A coating film was formed in the same manner as in Example 1 except that dimethylacrylamide was used as the monomer in step D and the concentration was performed to 313 g. A dispersion in which the surface-treated rutile titanium oxide particles were dispersed in the monomer was obtained.
[0110] Example 16
[0111] In addition to using 3-methacryloxypropyltrimethoxysilane as a silane coupling agent in step C, after adding the silane coupling agent and the alkaline additive, a dispersant (5 g of "DISPERBYK-111" manufactured by BYK Chemie Co., Ltd., Japan: 5 g per 100 parts by mass of TiO 2 The same operation as in Example 1 was performed except that the concentration was performed to 258 g in step D to obtain a dispersion in which surface-treated rutile titanium oxide particles were dispersed in a monomer, and then a coating film was formed.
[0112] Embodiment 17
[0113] In addition to using 3-methacryloxypropyltrimethoxysilane as a silane coupling agent in step C, after adding the silane coupling agent and the alkaline additive, a dispersant (5 g of "DISPERBYK-111" manufactured by BYK Chemie Co., Ltd., Japan: 5 g per 100 parts by mass of TiO 2 The same operation as in Example 1 was performed except that the concentration was performed to 229 g in step D to obtain a dispersion in which surface-treated rutile titanium oxide particles were dispersed in a monomer, and then a coating film was formed.
[0114] Embodiment 18
[0115] A coating film was formed in the same manner as in Example 1, except that 3-methacryloxypropyltrimethoxysilane was used as a silane coupling agent in step C, dimethylacrylamide was used as a monomer in step D, and the concentration was performed to 206 g. A dispersion in which surface-treated rutile titanium oxide particles were dispersed in the monomer was obtained.
[0116] Comparative Example 1
[0117] Except that dipentaerythritol hexaacrylate was used as a monomer in step D and the concentration was performed to 597 g, a dispersion liquid in which surface-treated rutile titanium oxide particles were dispersed in the monomer was obtained and evaluated in the same manner as in Example 1. The viscosity of the obtained dispersion liquid immediately after production was 9500 mPa·s, and the viscosity after the time test exceeded 10000 mPa·s. Therefore, the wet specific surface area could not be measured and a coating film could not be formed.
[0118] Comparative Example 2
[0119] A dispersion in which surface-treated rutile titanium oxide particles are dispersed in a monomer was obtained in the same manner as in Example 1, except that tin sulfate was not added in step B, and trimethylolpropane triacrylate was used as a monomer in step D and the concentration was performed to 547 g, and then a coating film was formed. The obtained dispersion had a high wet specific surface area and a high viscosity increase rate after a time test.
[0120] Comparative Example 3
[0121] A dispersion in which surface-treated rutile titanium oxide particles were dispersed in the monomer was obtained in the same manner as in Example 1 except that trimethylolpropane triacrylate was used as the monomer in step D and the concentration was performed to 1194 g, and then a coating film was formed. The obtained dispersion had a low ignition solid content and therefore a low refractive index.
[0122] Comparative Example 4
[0123] In addition to changing the amount of tin sulfate added in step B to 185.3 g (in terms of SnO 2 130 g: relative to 100 parts by mass of TiO 2 The same operation as in Example 1 was performed except that the monomer was 130 parts by mass), and n-octyl acrylate was used as the monomer and the concentration was performed to 958 g, to obtain a dispersion in which surface-treated rutile titanium oxide particles were dispersed in the monomer, and then a coating film was formed. The obtained dispersion had a high wet specific surface area and a high viscosity increase rate after a time test. In addition, due to the large amount of surface treatment, the refractive index was low.
[0124] Comparative Example 5
[0125] In step B, 413.8 g of sodium silicate No. 3 (in the form of SiO 2 120 g: relative to 100 parts by mass of TiO 2 120 parts by mass) (SiO 2 concentration of 29 mass %), and then 14.3 g of tin sulfate (SnO 2 10.0 g: relative to 100 parts by mass of TiO 2 After 10 parts by mass of SiO2 was added, the pH was adjusted to 6.0 using a 10% by mass sodium hydroxide aqueous solution. In this way, hydrated oxides of silicon and tin were precipitated on the surface of the core composed of titanium oxide particles to perform surface treatment. Next, the precipitate was filtered and washed, and water was added to adjust the concentration to obtain a precipitate prepared by 120 parts by mass of SiO2. 2 10 parts by mass of hydrated oxide of silicon (SnO 2 tin oxide hydrous oxide to 100 parts by mass (TiO 21000 g of an aqueous suspension of titanium oxide particles (TiO 2 The concentration was 10% by mass). In addition, in step D, tripropylene glycol diacrylate was used as a monomer and concentrated to 958 g. Except for these aspects, the same operation as in Example 1 was performed to obtain a dispersion in which surface-treated rutile titanium oxide particles were dispersed in the monomer, and a coating film was formed. The obtained dispersion had a high wet specific surface area and a high viscosity increase rate after a time test. In addition, due to the large amount of surface treatment, the refractive index was low.
[0126] Comparative Example 6
[0127] In step C, 1000 g of isopropanol and 1000 g of butanone were added to the aqueous suspension of 1000 g of the surface-treated titanium oxide particles obtained in step B. Then, while further adding butanone, ultrafiltration was performed to replace the dispersion medium with butanone, and a total amount of 1000 g (TiO 2 In step C, neither silane coupling agent nor alkaline additive is added. In step D, 500 g of n-octyl acrylate is added as a monomer, and 70 g (relative to 100 parts by mass of TiO 2 "DISPERBYK-111" manufactured by BYK Chemie, Japan (70 parts by mass) was used as a dispersant. N-octyl acrylate was further added and concentrated with an evaporator to replace it with n-octyl acrylate. By dispersing the slurry with a bead mill, 915 g of a dispersion in which surface-treated rutile titanium oxide particles were dispersed in a monomer was obtained. In addition to these aspects, after the dispersion was obtained in the same manner as in Example 1, a coating film was formed. The obtained dispersion had a high wet specific surface area and a high viscosity increase rate after a time test. In addition, the haze of the dispersion and the coating film was large.
[0128] Comparative Example 7
[0129] 300 g of titanium oxide powder "MICROTITANIUM DIOXIDE MT-05" manufactured by Tayca Co., Ltd. and 90 g of dispersant "DISPERBYK-111" manufactured by BYK Chemie Co., Ltd. of Japan were added to 610 g of diphenyl methyl acrylate to prepare a slurry. Here, the titanium oxide powder "MT-05" is titanium oxide particles surface-treated with hydrated oxides of silicon and aluminum. After the slurry was dispersed with a bead mill to obtain 1000 g of a dispersion in which rutile titanium oxide particles were dispersed in a monomer, a coating film was formed. The average particle size of the titanium oxide in the obtained dispersion was large, and the haze of the coating film was very large.
[0130] Comparative Example 8
[0131] In step C, 1000 g of isopropanol and 1000 g of butanone were added to the aqueous suspension of 1000 g of the surface-treated titanium oxide particles obtained in step B. Then, while further adding butanone, ultrafiltration was performed to replace the dispersion medium with butanone, and a total of 200 g (TiO 2 Next, 25 g of 3-acryloxypropyltrimethoxysilane (100 parts by mass of TiO2) as a silane coupling agent was added. 2 25 parts by mass) and 5 g of tert-butylamine as a basic additive (relative to 100 parts by mass of TiO 2 5 parts by mass), a butanone dispersion of 230 g of titanium oxide particles with surface treatment was obtained. By adding 100 g of benzyl acrylate to the dispersion, a dispersion in which surface-treated rutile titanium oxide particles were dispersed in the monomer was obtained. Except for these aspects, the dispersion was obtained in the same manner as in Example 1, and then a coating film was formed. The obtained dispersion had a high solvent content and a high solvent residual rate of the coating film.
[0132] [Table 1]
[0133]
[0134] [Table 2]
[0135]
[0136] [Table 3]
[0137]
Claims
1. A dispersion comprising titanium oxide particles, a silane coupling agent and a monomer having a polymerizable functional group; The titanium oxide particles are particles obtained by surface treating a core of rutile titanium oxide with a hydrated oxide of tin or zirconium, wherein the content of titanium oxide in the particles is 70 to 95% by mass as calculated as TiO2, and the content of hydrated oxide of tin or zirconium in the particles is 5 to 30% by mass as calculated as SnO2 or ZrO2. The viscosity of the above monomer at 25°C is 100 mPa·s or less, The dispersion was calcined at 925°C for 2 hours to obtain a solid content of 15 to 55% by mass. In the dispersion, the content of the silane coupling agent is 2 to 15% by mass, the content of the monomer is 30 to 85% by mass, the content of the organic solvent having no polymerizable functional group is 10% by mass or less, and The viscosity of the dispersion at 25° C. is 500 mPa·s or less.
2. The dispersion according to claim 1, wherein The ignition solid content is 15 to 45% by mass, and the content of the monomer in the dispersion is 50 to 85% by mass.
3. The dispersion according to claim 1 or 2, wherein The wet specific surface area of the titanium oxide particles measured by pulse NMR is 20 to 150 m 2 / g.
4. The dispersion according to any one of claims 1 to 3, wherein The titanium oxide particles are particles that have been debonded using an alkaline additive.
5. The dispersion according to any one of claims 1 to 4, wherein The average particle size of the titanium oxide particles in a liquid having a solid content on burning of 5% by mass obtained by diluting the dispersion with the monomer is 20 to 50 nm.
6. The dispersion according to any one of claims 1 to 5, wherein The haze of a liquid having a solid content on ignition of 5% by mass obtained by diluting the dispersion with the monomer at an optical path length of 10 mm is 40% or less.
7. A curable sealing material comprising the dispersion according to any one of claims 1 to 6. The sealing material according to claim 7 , which is used for sealing an optical element.
9. A solidified product obtained by solidifying the dispersion according to any one of claims 1 to 6. 10 . The cured product according to claim 9 , which has a refractive index of 1.6 or more at 20° C. and 633 nm.
11. The cured product according to claim 9 or 10, wherein The residual rate of the organic solvent is 0.1 to 10% by mass.
12. An optical element sealed with the cured product according to any one of claims 9 to 11.
13. The method for producing a dispersion according to any one of claims 1 to 6, comprising removing water from the aqueous dispersion of the titanium oxide particles and replacing it with the organic solvent, adding the silane coupling agent to the obtained dispersion, and then removing the organic solvent and replacing it with the monomer.
14. The method for producing a dispersion according to claim 13, wherein: The silane coupling agent and the alkaline additive are added to the dispersion liquid replaced with the organic solvent to dissociate the titanium oxide particles, and then the organic solvent is removed and replaced with the monomer.
Citation Information
Patent Citations
Curable composition and compound
JP2020026515A
Epoxy polymerizable composition and organic el device
WO2013005441A1
Resin composition
WO2017170888A1
Rutile-type titanium oxide organosol, method for producing rutile-type titanium oxide organosol, high refractive index coating-forming composition using said rutile-type titanium oxide organosol, and optical element
WO2021193262A1